Using a chemiresistor-based alkane sensor to distinguish exhaled breaths of lung cancer patients from subjects with no lung cancer - Tan, Jiunn-Liang; Yong, Zheng-Xin; Liam, Chong-Kin (Journal of Thoracic Disease, 2016)
Background: Breath alkanes are reported to be able to discriminate lung cancer patients from healthy people. A simple chemiresistor-based sensor was designed to respond to alkanes by a change in resistance measured by a digital multimeter connected to the sensor. In preclinical experiments, the sensor response was found to have a strong positive linear relationship with alkane compounds and not responsive to water. This study aimed to determine the ability of the alkane sensor to distinguish the exhaled breaths of lung cancer patients from that of chronic obstructive pulmonary disease (COPD) patients and control subjects without lung cancer. Methods: In this cross-sectional study, 12 treatment-naive patients with lung cancer, 12 ex- or current smokers with COPD and 13 never-smokers without lung disease were asked to exhale through a drinking straw into a prototype breath-in apparatus made from an empty 125 mL Vitagen® bottle with the chemiresistor sensor attached at its inside bottom to measure the sensor peak output (percentage change of baseline resistance measured before exhalation to peak resistance) and the time taken for the baseline resistance to reach peak resistance. Results: Analysis of multivariate variance and post-hoc Tukey test revealed that the peak output and the time to peak values for the lung cancer patients were statistically different from that for both the COPD patients and the controls without lung disease, Pillai’s Trace =0.393, F=3.909, df = (4, 64), P=0.007. A 2.20% sensor peak output and a 90-s time to peak gave 83.3% sensitivity and 88% specificity in diagnosing lung cancer. Tobacco smoking did not affect the diagnostic accuracy of the sensor. Conclusions: The alkane sensor could discriminate patients with lung cancer from COPD patients and people without lung disease. Its potential utility as a simple, cheap and non-invasive test for early lung cancer detection needs further studies.